Preparation and Characterization of Cu(In,Ga)Se2 Thin Films by Selenization of Cu0.8Ga0.2 and In2Se3 Precursor Films - Jiang Liu; Da-Ming Zhuang; Ming-Jie Cao; Chen-Yue Wang; Min Xie; Xiao-Long Li (International Journal of Photoenergy)
Se-containing precursor films with two different compositions were prepared by magnetron sputtering from and targets, and then were selenized using Se vapor. The effects of precursor composition and selenization temperature on the film properties were investigated. The results show that Se phase plays a critical role in film growth and electrical properties of CIGS films. The Cu-rich films exhibit different surface morphology and better crystallinity, as compared to the Cu-poor films. All the CIGS films exhibit p-type conductivity. The resistivity of the Cu-rich films is about three orders of magnitude lower than that of the Cu-poor films, which is attributed to the presence of p-type highly conductive Se phase.